Implementasi Akuntabilitas Publik dalam Mewujudkan Good Governance: Analisis Sistem SAKIP dan Kerangka Regulasi di Indonesia - Suci Ramadhani Suci; Jumiati Jumiati; Boni Saputra (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
The implementation of a public accountability system can serve as an indicator of success in realizing good governance in Indonesia. This public accountability can later improve transparency, integrity, and the quality of public services and prevent the practice of corruption, collusion, and nepotism in government administration. In addition, this article is designed to identify the obstacles faced in implementing public accountability and provide strategic recommendations to make governance more effective, responsive, and accountable to the community.Thus, this article is expected to contribute to the development of an accountability system that supports the achievement of a clean, transparent, and integrity government.